Investigating the Relationship between Factors Affecting Hip Fracture and Its Consequences in Imam Khomeini Hospital Complex during 2017-2020 - Mahya Jafarnejad; Esmaeil Mohammadnejad; Leila Sayadi; Shima Haghani; Reza Ghanei Gheshlagh; Afzal Shamsi (Tehran University of Medical Sciences, 2022)
Background and Aim: Fractures and dislocations of the femur are a common and disruptive public health problem worldwide. One of the most common ways is to identify the factors associated with common outcomes that increase mortality, length of hospital stay, and postoperative complications. By identifying these factors, the adverse outcomes of elderly hip fractures can be prevented. Therefore, the aim of this study was to determine the relationship between factors affecting hip fracture and its consequences.  Materials and Methods: The present study was a descriptive cross-sectional observational study. The study population in this study included patients with hip fractures. Patients' information was examined between 2017-2020 years. Data were analyzed by SPSS applying descriptive statistics, Fisher Exact test, chi-square, independent t-tests, and analytical regression. Results: The results showed that in this study, the majority of patients with hip fracture had an underlying disease (73.9%). The most common underlying diseases in patients included high blood pressure (20.7%), diabetes (13.2%) and heart diseases (10.5%). The most common causes of death was include old age (40.4%), prevalence of covid-19 (20.2%), heart attack (11.7%), pulmonary embolism (10.6%) and surgical wound infection (10.6%). The most common cause of hip fracture was osteoporosis (26.3%) and falling from a height (24.7%). Also level of education (P=0.0001), causes of fracture (P=0.001), type of anesthesia (P=0.001), history of hospitalization in special wards (P=0.001), readmission (P=0.0001), age (P=0.001) and level of self-care (P=0.001) were significantly associated with elderly mortality. There was a significant relation between type of surgery (P=0.038), history of hospitalization in intensive care units (P=0.001), history of blood transfusion (P=0.021) and level of self-care (P=0.001) with length of hospital stay of fractured elderly hip. Conclusion: It can be concluded that by identifying the factors affecting the length of hospital stay, surgical wound infection and mortality of the patients with hip fractures, witness better surgery results, shorter hospital stay, less postoperative complications and reduced death. Some factors such as osteoporosis are preventable, which can be prevented with timely education.